Interrelationships of the Intestinal Microbiome, Trimethylamine N-Oxide and Lipopolysaccharide-Binding Protein with Crohn’s Disease Activity - Yelena Laryushina; Nadezhda Samoilova-Bedych; Lyudmila Turgunova; Alexandr Marchenko; Yermek Turgunov; Samat Kozhakhmetov; Maxat Suieubayev; Nurislam Mukhanbetzhanov; Nadezhda Kabdulina (Pathogens)
Crohn’s disease (CD) is a multifactorial inflammatory bowel disease whose pathogenetic mechanisms are a field of ongoing study. Changes in the intestinal microbiome in CD may influence metabolite production and reflect the disease’s severity. We investigate the relationship between trimethylamine N-oxide (TMAO) and lipopolysaccharide-binding protein (LPS) levels and changes in the gut microbiome in patients with CD of various degrees of activity. Methods: In total, 29 CD patients and 15 healthy individuals were investigated for their levels of TMAO by HPLC-MS, and LPS protein by ELISA and metagenomic 16 s-sequencing of feces was performed. Results: We found significant differences in TMAO levels in patients in the remission/mild and moderate/severe groups compared to the control group (p = 0.02 and p = 0.014), changes in alpha diversity with the Shannon index (p = 0. 0151 and p = 0.0018) and in beta diversity (ANOSIM p = 0.009 and PERMANOVA p = 0.005) in both groups compared to controls. Strongly positive correlations in TMAO levels and mixed correlations of LPS with alpha diversity metrics were found, as well as significant correlations with microbiota species. Conclusions: Changes in the level of metabolites may reflect specific disturbances in the composition of the intestinal microbiome at different degrees of severity of CD.